Antecedents of Sales Performance in the Malaysian Commercial Banking Industry - Koay, Huey Sian; Sany Sanuri bin Mohd Mokhtar; Mohd Zainol Abidin bin Adam (Journal of Technology Management and Business, 2023)
Sales performance is important to every salesperson as a key performance indicator for their yearly performance. However, nearly half of them are still unable to fulfill it. Hence, this study aims to investigate the personal factors that influence the sales performance of salespersons in the banking industry. The study examines the direct relationship between improvisational behavior, adaptive selling, and self-efficacy in relation to sales performance among salespersons working in various local commercial banks in Malaysia. In these banks, despite the increasing importance of sales performance, almost half of the salespeople still fail to meet their annual performance target. A survey design with clustered random samples was utilised for this study. Questionnaires were used to collect data from salespersons in Malaysian commercial banks in the Klang Valley. The data was then analyzed using Structural Equation Modelling (SEM) with SmartPLS 4.0. In this study, three hypotheses were developed and tested through a two-stage evaluation. The results show that improvisational behavior is the most significant predictor of sales performance, followed by adaptive selling and self-efficacy. The results of the study provide managers with novel concepts to understand the factors that influence a salesperson’s sales performance in the Malaysian banking sector.